Outbreak of bacterial meningitis after spinal anaesthesia in Bangladesh - Akhtaruzzaman, AKM; Akhtar, Begum Maksuda Farida; Roy, Joysree; Laskar, Manzoorul Hoque; Dhar, Satyajit; Mandal, Md Badrul Alam; Saleh, Ahmed Abu (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Iatrogenic meningitis following spinal anaesthesia is very rare. Recently we have experienced severe headache, vomiting, fever, restlessness, nuchal rigidity and altered level of consciousness 5-6 hours after spinal anaesthesia in one hundred and nineteen patients diagnosed as iatrogenic bacterial meningitis during the period of September 2008 to March 2009. Patients were successfully treated with Inj. Ceftriaxone 2gm BID for 14 days, Inj. Dexamethasone 20mg daily in four divided dose for five days. Purulent CSF, high cell count (1570mm-3), elevated protein level (269mg/dl) and normal glucose (57mg/dl) levels in CSF were noted. There were 5 (4.2%) cases of mortality. No causative organisms were isolated from CSF, blood of the affected patients and anaesthetic agent used for the block. In conclusion, the cause of meningitis was diagnosed as bacterial in origin though no organism was isolated. DOI: http://dx.doi.org/10.3329/jbsa.v22i1.18084 Journal of BSA, 2009; 22(1): 5-11